2016
DOI: 10.1155/2016/2819862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Coadministration of Ascorbic Acid with Ling Zhi Preparation on Pharmacokinetics of Ganoderic Acid A in Healthy Male Subjects: A Randomized Crossover Study

Abstract: The objective of this randomized, open-label, single-dose, two-phase crossover study was to determine the effect of ascorbic acid on pharmacokinetics of ganoderic acid A, an important biologically active triterpenoid compound with anticancer activities, following oral administration of water extract of fruiting bodies of Ling Zhi in 12 healthy male subjects. Each subject was randomized to receive either one of the two regimens: (1) a single dose of 3,000 mg of the Ling Zhi preparation or (2) a single dose of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…For example, GAA showed an antitumor effects on human hepatocellular carcinoma cells as cell proliferation and invasion were repressed, whereas apoptosis was enhanced after GAA treatments (Wang, Sun, Tai, & Wang, 2017). The inhibitory effects of GAA on CDK4 expression, secretion of urokinase plasminogen activator, and farnesyl protein transferase were well documented previously (Tawasri, Ampasavate, Tharatha, Chiranthanut, & Teekachunhatean, 2016). A large body of studies has reported the protective role of G. lucidum extract in neurons (Ren et al, 2018;Zhang et al, 2011).…”
mentioning
confidence: 72%
“…For example, GAA showed an antitumor effects on human hepatocellular carcinoma cells as cell proliferation and invasion were repressed, whereas apoptosis was enhanced after GAA treatments (Wang, Sun, Tai, & Wang, 2017). The inhibitory effects of GAA on CDK4 expression, secretion of urokinase plasminogen activator, and farnesyl protein transferase were well documented previously (Tawasri, Ampasavate, Tharatha, Chiranthanut, & Teekachunhatean, 2016). A large body of studies has reported the protective role of G. lucidum extract in neurons (Ren et al, 2018;Zhang et al, 2011).…”
mentioning
confidence: 72%